PERSONAL, ACADEMIC AND DEPARTMENTAL CORRELATES OF RESEARCH PRODUCTIVITY: A REVIEW OF LITERATURE - A. N., Zainab (Malaysian Journal of Library and Information Science, 1999)
Reviews published sources on research productivity under two broad categories, general measures of research productivity and correlates of publication productivity. The latter cover studies on three broad determinants comprising (1) personal, (2) academic, (3) and departmental correlates considered to be related to academic publication productivity.